Pengaruh pemberian thidiazuron dan NAA pada media MS terhadap regenerasi eksplan nodal vanili (Vanilla Planifolia Andrews) secara in vitro - Ardyansah, Muhammad Ikrom; Kusbianto, Dwi Erwin; Suud, Hasbi Mubarok; Rosyady, Muhammad Ghufron (Jurnal Agrotek Ummat, 2024)
Vanilla is a commodity with high economic value that belongs to the Orichidaceae family. One of the problems in vanilla cultivation is unhealthy seedlings and mother plants due to Fusarium oxysporum infection. In vitro plant propagation is an alternative because it uses a small part of the plant on sterile media so that it becomes a healthy plant. The objective of this study was to determine the effect of thidiazuron and NAA on the growth response of vanilla (Vanillaplanifolia Andrews) node explants in vitro. This research method uses RAL, which consists of two factors. Thidiazuron at concentrations of 0, 0.5, and 1 ppm combined with NAA at concentrations of 0, 1, 2 ppm. The data were analyzed by ANOVA at 5% level of significance, followed by BNT (Least Significant Difference) test at 5% level of significance. The results showed that the interaction between the administration of thidiazuron and NAA on the response of vanilla (Vanilla planifolia Andrews) nodule explants in vitro had a significant effect on the variables of shoot length and root length. In conclusion, the combined treatment of thidiazuron concentration 0.5 ppm and NAA concentration 1 ppm (T1N1) showed the best trend.